1988
DOI: 10.1007/bf00291676
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of a polymorphic marker for the type III collagen gene (COL3A1) to atypical autosomal dominant Ehlers-Danlos syndrome type IV in a large Belgian pedigree

Abstract: We have examined a large family in which eleven members have a form of autosomal dominant Ehlers-Danlos syndrome type IV. Analysis of fibroblast cultures from affected individuals showed a partial deficiency of type III collagen production. The protein produced was, however, normal in all aspects examined. Using a restriction site polymorphism associated with the structural gene for human type III collagen (COL3A1), we have found tight linkage between the low frequency polymorphic allele and the clinical expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…We have previously described a large family with EDS IV (Matton et al 1982), which was shown to be linked to an AvaII polymorphism in the COL3A1 gene (Nicholls et al 1988). In contrast to typical EDS IV patients, fibroblasts from affected members of this family secreted near normal amounts of an apparently normal type III collagen.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…We have previously described a large family with EDS IV (Matton et al 1982), which was shown to be linked to an AvaII polymorphism in the COL3A1 gene (Nicholls et al 1988). In contrast to typical EDS IV patients, fibroblasts from affected members of this family secreted near normal amounts of an apparently normal type III collagen.…”
Section: Introductionmentioning
confidence: 92%
“…More recently, cases of EDS IV have been shown to be linked to the type III collagen gene COL3A1 (Tsi-* Present address: Institute for Animal Health, Compton, Berks, RG16 ONN, UK Offprint requests to: A. J. Richards pouras et al 1986;Nicholls et al 1988), and a number of mutations have been characterised. These include large deletions (Superti-Furga et al 1988McGookey et al 1989;Lee et al 1991b;Vissing et al 1991), point mutations (Tromp et al 1989a(Tromp et al , 1989bRichards et al 1991) and aberrant splicing ; Kuivaniemi et al 1990;Cole et al 1990; Lee et al 1991a).…”
Section: Introductionmentioning
confidence: 98%
“…Articular hypermobility is restricted to the small joints [Byers et al, 19831. Fibroblasts cultured from virtually all individuals with EDS type IV have defects in the synthesis, structure, or secretion of type I11 procollagen [Pope et al, 1975;Byers and Holbrook, 1985;Stolle et al, 1985;Tsipouras et al, 1986;SupertiFurga and Steinmann, 1988;Temple et al, 1988;Nicholls et al, 1988;Superti-Furga et al, 1989;Tromp et al, 19891.…”
Section: Introductionmentioning
confidence: 97%
“…The Ehlers Danlos syndrome type IV was added to the map at IIGM9.5 because of close linkage to COI.3A1 (Tsipouras et al, 1986;Nicholls et al, 1988;De Pacpe et al, 1988). Direct evidence that this disease is caused by deletions or single base mutations in the COL3A1 gene has now been found (SupertiFurga et al, 1988;Kuivanicmi et al, HGM10), as suggested by earlier work on the protein.…”
Section: Changes and Inconsistenciesmentioning
confidence: 99%